A Chinese Herbal Compound Fertilizer Improved the Soil Bacterial Community and Promoted the Quality of Chrysanthemum morifolium ‘Huangju’ - Hongliang Li; Hongyao Qu; Huaqiang Xuan; Bei Liu; Lixiang Zhu; Xianchao Shang; Yi Xie; Li Zhang; Long Yang; Ling Yuan; Sitakanta Pattanaik; Li Xiang; et al. (Agronomy)
Chrysanthemum morifolium, ‘Huangju’, is a golden chrysanthemum used for making tea. Limited by land resources, the continuous cropping of Chrysanthemum morifolium ‘Huangju’ has led to serious soil issues, which affects its yield and quality. In this study, different ratios of traditional Chinese medicine compound fertilizers were used to regulate the soil environment in order to achieve the green prevention and control of continuous cropping obstacles of the golden chrysanthemum. Five treatments were set up in the experiment: the control (CK) and different proportions of the Chinese herbal compound fertilizer T1, T2, T3, and T4. After the application of the traditional Chinese medicine compound fertilizer, the physical and chemical soil properties of the golden chrysanthemum were changed to varying degrees, resulting in an increased yield of golden silk chrysanthemum and an improved tea quality. This preliminary study on the application of the traditional Chinese medicine compound fertilizer T2 and T3—that is, Sophora flavescens–Stemona sessilifolia–Mentha haplocalyx–Perilla frutescens–Artemisia annua at ratios of 2:1:2:1:1.5 and 3:1:3:1:2—treatments provided the best results and can be further developed to alleviate the continuous cropping obstacles of fertilizers.